Precision and efficiency in solid-state pseudopotential calculations. (December 2018) - Prandini, Gianluca; Marrazzo, Antimo; Castelli, Ivano; Mounet, Nicolas; Marzari, Nicola
Abstract Despite the enormous success and popularity of density-functional theory, systematic verification and validation studies are still limited in number and scope. Here, we propose a protocol to test publicly available pseudopotential libraries, based on several independent criteria including verification against all-electron equations of state and plane-wave convergence tests for phonon frequencies, band structure, cohesive energy and pressure. Adopting these criteria we obtain curated pseudopotential libraries (named SSSP or standard solid-state pseudopotential libraries), that we target for high-throughput materials screening ("SSSP efficiency") and high-precision materials modelling ("SSSP precision"). This latter scores highest among open-source pseudopotential libraries available in the Δ-factor test of equations of states of elemental solids. Density functional theory A protocol for testing pseudopotentials Curated pseudopotential libraries obtained by systematic testing of available pseudopotentials are obtained using a newly proposed testing protocol. Density functional theory is very popular, but little attention has been devoted so far to the verification of the underlying pseudopotentials and projector augmented-wave approximations. The issue of performance is also of importance, as smoother pseudopotentials would enable faster calculations. Now, Nicola Marzari and colleagues from the Ecole Polytechnique Fédérale de Lausanne in Switzerland introduce a testing protocol for pseudopotentials in publicly available libraries, and select the optimal pseudopotential for 85 elements. The protocol includes both a verification step and performance evaluation step. Finding the right balance between precision and performance is particularly important for high-throughput materials searches, which are currently the focus of big efforts worldwide